2023
DOI: 10.3171/2022.7.spine22592
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 2-year clinical outcome trajectories in patients undergoing anterior cervical discectomy and fusion for spondylotic radiculopathy

Abstract: OBJECTIVE Anterior cervical discectomy and fusion (ACDF) is often described as the gold standard surgical technique for cervical spondylotic radiculopathy. Although outcomes are considered favorable, there is little prognostic evidence to guide patient selection for ACDF. This study aimed to 1) describe the 24-month postoperative trajectories of arm pain, neck pain, and pain-related disability; and 2) identify perioperative prognostic factors that predict trajectories representing poor clinical outcomes. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The observation that worse mental health is associated with greater pain intensity and magnitude of incapability throughout the recovery course, independent of arthroplasty type, confirms that comfort and capability achieved by shoulder arthroplasty can be limited by modifiable mindset factors and supports the comprehensive, biopsychosocial treatment of musculoskeletal illness. This aligns with other studies of recovery trajectories after musculoskeletal surgery finding that unhealthier mindsets are associated with greater pain [11] and capability [14,15] at baseline and until 2 years after surgery, as well as less likelihood that a patient will gain substantial benefits from surgery [37]. Baseline pain intensity was worse on average for people requesting revision arthroplasty [12].…”
Section: Trajectories Of Pain Intensity and Magnitude Of Incapabilitysupporting
confidence: 85%
See 2 more Smart Citations
“…The observation that worse mental health is associated with greater pain intensity and magnitude of incapability throughout the recovery course, independent of arthroplasty type, confirms that comfort and capability achieved by shoulder arthroplasty can be limited by modifiable mindset factors and supports the comprehensive, biopsychosocial treatment of musculoskeletal illness. This aligns with other studies of recovery trajectories after musculoskeletal surgery finding that unhealthier mindsets are associated with greater pain [11] and capability [14,15] at baseline and until 2 years after surgery, as well as less likelihood that a patient will gain substantial benefits from surgery [37]. Baseline pain intensity was worse on average for people requesting revision arthroplasty [12].…”
Section: Trajectories Of Pain Intensity and Magnitude Of Incapabilitysupporting
confidence: 85%
“…Variations in pain intensity and magnitude of incapability have a limited association with pathophysiologic severity and are accounted for largely by variation in unhelpful thoughts and distress about symptoms [11,13,14,24]. Recent evidence suggests that recovery of comfort and capability over the course of 2 years after injury and surgery is tied to baseline mental health status [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between race and delays in treatment has been noted previously by Elsamadicy et al 24 , who found race to be a predictor of the temporal delay of cervical stenosis treatment. According to Hébert et al, these delays in treatment have been shown to worsen surgical outcomes across the board in those needing cervical spine fusions 25 . Many studies analyzing not only cervical spine fusion but also spine surgery in general have also identified racial disparities in both utilization and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hébert et al, these delays in treatment have been shown to worsen surgical outcomes across the board in those needing cervical spine fusions. 25 Many studies analyzing not only cervical spine fusion but also spine surgery in general have also identified racial disparities in both utilization and outcomes. Amen et al 26 found that white patients were nearly twice as likely as Black patients to utilize outpatient cervical spine procedures, while another study by Elsamadicy et al 27 found that Black patients had higher lengths of stay and complication rates in cervical spine fusions.…”
Section: Racial Disparities In Access To Cervical Spine Fusionsmentioning
confidence: 99%